The BLUE Framework: Designing User-Centered In-Product Feedback for Large Scale Applications - Hillman, Serena; Jain, Samira; Jienjitlert, Vichita; Bach, Paula M (Proceedings of the ACM Conference on Human Factors in Computing Systems (CHI) 2022, 2022)
In-product feedback mechanisms allow for capturing user feedback while the user is engaging with the product or service. Traditionally in-product feedback has focused on metrics such as Net Promoter Score (NPS) [21] and Customer Satisfaction (CSAT) [5] which look to measure customer loyalty or overall product satisfaction. By introducing complementary user experience (UX) metrics that are focused on user outcomes, UX teams have greater insight into measuring the successes or challenges of their users in the context of use. This case study describes and discusses the process employed and the lessons learned while designing and implementing a user-centered in-product feedback system. We specifically call out challenges and opportunities around aligning with business outcomes, navigating current frameworks, unlocking self-serve data to stakeholders, informing strategy, and feeding additional research. In conclusion, we present these learnings as a framework, dubbed BLUE, to help other UX teams create in-product feedback mechanisms.